Factors Associated with Body Weight Status Among Iranian Adolescents Studing in Kuala Lumpur, Malaysia - Zarei, Maryam (2011)
A cross- sectional study was conducted to determine factors associated with body weight status of Iranian postgraduate students in Universiti Putra Malaysia (UPM), Malaysia. A self- administered questionnaire addressing socio-demographic factors, nutritional knowledge, weight management knowledge, life style factors and dietary intake was completed by 210 female and male students aged between 22-55 years. Anthropometric factors (height, weight, waist and hip circumferences and body fat composition) were measured using standard procedures. Body Mass Index (BMI) and Waist Hip Ratio (WHR) were calculated for each subject. WHO classifications (WHO, 2000; WHO, 2004) were used for categorizing WHR and BMI respectively. The respondents comprised 110 (53.4%) females and 100 (47.6%) males. Results indicated that 7.1% of all respondents were underweight, 64.8% normal weight,24.3% overweight and 3.8% obese. Two thirds of the respondents or 140 (66.7%) were single and only 70 (33.3%) of the respondents were married. About 109 (51.9%) of the respondents were pursuing their Masters degree while 101 (48.1%) were pursuing their PhD degree. Sex was associated with BMI ((χ2=12.200, p<0.01) in this study. Among male respondents, the proportion of overweight and obese was higher than female respondents. Prevalence of overweight and obesity were 35.0% and 4.0% in males as compared to 14.5% and 3.6% of the female respondents. For nutritional knowledge the mean score for male respondents was 25.9±5.8 whereas the mean score for female respondents was 27.3±5.1. Also, 70.5% of the respondents were categorized as having a low level of nutritional knowledge, 26.7% of the respondents had moderate level of nutritional knowledge and only 2.8% of the respondents had a high level of nutritional knowledge. There was no significant relationships between BMI and nutritional knowledge (Rho=-0.032, p>0.05). For weight management knowledge the mean score for male respondents was 5.7±2.3; whereas the mean score for female respondents was 6.6±1.5. Most of the respondents, 55.7% were categorized as having low level of weight management knowledge, 41.4% of the respondents had moderate level of weight management knowledge and only 2.9% respondents had a high level of weight management knowledge. There was no significant correlation between BMI and weight management knowledge (Rho=0.085, p>0.05). About 64 (30.5%) of the respondents comprising of 46 (46.0%) males and 18 (16.4%) females have tried smoking. There were 146 (69.5%) respondents who were non-smokers. There was no significant relationships between BMI categories and smoking (χ2=2.467, p>0.05). Overall, 19.1% of the respondents had high physical activity. About 25.7% of the respondents had moderate physical activity. However, 55.2% of the respondents had low activity during the previous week. There was correlation between BMI with physical activity (r=-0.15, p<0.05). Bivariate analysis showed statistically significant correlation between protein (Rho=0.677, p<0.01), carbohydrate (Rho=0.848, p<0.01), fat (Rho=0.865, p<0.01), fiber (Rho=0.743, p<0.01), vitamin C (Rho=0.136, p<0.05), calcium (Rho=0.352, p<0.01) and iron (Rho=0.551, p<0.01) with BMI. There were relationships between body fat (Rho=0.235, p<0.01), waist circumference (Rho= 0.725, p<0.01), hip circumference (Rho= 0.721, p<0.01) and WHR (Rho=0.245, p<0.01) with BMI. Multivariate analysis found a factor contributing significantly to body weight status in postgraduate Iranian students was physical activity which explained about 10% of the variation in BMI (R= 0.31, R2=0.10; F=22.345, p=0.000). The present study provided an insight into factors that contribute to body weight status of postgraduate Iranian students in UPM. These findings show the need for a nutrition promotion program for the Iranian students to help them change their negative food habits and improve their lifestyle.